Amplified Thermopower Waves in Large‐Area Carbon–Nanotube/Fuel Composites via Thermal Decomposition of Sodium Nitrate. Issue 6 (27th January 2017) - Hwang, Hayoung; Shin, Dongjoon; Yeo, Taehan; Choi, Wonjoon
Abstract : Advancement of micro‐nanotechnology has accompanied the need for developing new energy sources. Thermopower waves (TWs), which use the combustion of high‐energy‐density fuels surrounding micro‐nanostructured materials, can implement the direct conversion between chemical–thermal–electrical energy on a small scale as a potential energy source for the next‐generation devices. Herein, the enhancement of TWs by the decomposition of sodium nitrate for additional thermal energy and charge suppliers in combustion is reported. The hybrid composites of carbon nanotubes and nitrocellulose with and without NaNO3 crystals are prepared as TWs generators. The thermal energy and electrons supplied through the decomposition of NaNO3 crystals amplify the voltage (≈732 mV at 23.3 Ω electrical resistance) and current by a factor of seven compared to the composite without NaNO3 crystals, while the maximum temperature in combustion is increased by 90 °C. The real‐time analyses of the dynamic change of the internal resistance and current for TWs can elucidate the origin of the enhanced energy generated using the hybrid composites. The advanced TWs obtained by the decomposition of the charge suppliers in this work will contribute to facilitating further development of TW‐based devices and understanding the underlying physics of the interaction between micro‐nanostructured materials and combustion on a small scale. Abstract : The decomposition of sodium nitrate for additional thermal energy and charge suppliers in combustion enables the further enhancement of energy generation from thermopower waves in a hybrid composite comprising a multiwalled carbon nanotube film, sodium nitrate, and nitrocellulose. The real‐time analyses of the internal resistance and current elucidate the origin of the enhanced energy generated using the sodium nitrate.